Organization Of International Exhibitions And Uzbekistan's Participation In Them (Eurasian Research Bulletin, 2024)
The article is focused on the use of agricultural lands in protected zones of highways. Legislative restrictions aimed at protecting road infrastructure and ensuring traffic safety are considered. Particular attention is paid to the need for a balance between the development of transport infrastructure and the rational us The social development of each nation and its place in world civilization is manifested in cultural exchange. That is why the most advanced aspects of the national culture of a people are measured by their cultural lifestyle and cultural ties. International exhibitions also occupy a special and significant place in the chain of such a process. The general meaning of the concept of "exhibition" is that it is understood as a public demonstration of material and spiritual wealth and products created by human labour. Industrial, and agricultural products, works of art, books, and others can be exhibited.  of agricultural land.